PENERAPAN E-GOVERNMENT DENGAN MODEL GOVERMENT TO CITIZEN MELALUI APLIKASI MEDAN SMART CITY - Novira Annissa Yusdartono; Siti Hazzah Nur R (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Smart city is defined as a city concept that integrates physical, social, and economic infrastructure through information and communication technology (ICT). Government to Citizen (G2C) can be associated with Smart city because G2C is part of Smart city implementation. Medan City is one of the cities that implements Smart city by issuing an application called Medan Smart City (Mercy) but its implementation in the field is still not optimal. This study aims to analyze the implementation of G2C in Medan City through the Mercy application. The research conducted in the form of field observations and interviews with 10 people to determine the level of causes of the suboptimal implementation of G2C. The results obtained that the cause of the suboptimal implementation of G2C is due to the lack of public knowledge about this application and the application is too complicated. This is known based on interviews conducted with 6 people who do not have knowledge while 4 people have heard about this application. The Medan City Government's prevention efforts include online and offline outreach and a simplified application. These improvements are evident in the simplified features of the app. Furthermore, satisfaction with the app's improvements is evidenced by positive comments from a resident interviewed previously.